Unboxing the primary English teacher's TPACK profile: instrumental design and validation - Wahyuni, Sri; Etfita, Fauzul; Dafit, Febrina; Asnawi, Asnawi (Intelektual Pustaka Media Utama, 2024)
Numerous researchers have developed technological pedagogical content knowledge (TPACK) instruments for English language teaching; however, a valid and reliable instrument to unbox the primary English language teacher's TPACK profile from graduates of the primary school teacher education study program does not yet exist. Consequently, this study aimed to design and validate a questionnaire to unbox the primary English language teacher's TPACK profile. This study used a mixed-methods approach. First, qualitative methods were employed to verify and validate the content of each construct. The items were generated through experts' and a primary English teacher’s reviews. As a quantitative method, the questionnaire was then validated through explanatory factor analysis (EFA). The result of EFA yielded a comprehensive set of 40 items: technological knowledge (TK) section (consisting of 5 items), content knowledge (CK) section (consisting of 6 items), pedagogical knowledge (PK) section (consisting of 6 items), pedagogical content knowledge (PCK) section (consisting of 5 items), technological content knowledge (TCK) section (consisting of 5 items), technological pedagogical knowledge (TPK) section (consisting of 7 items), and TPACK section (consisting of 5 items). The reliability coefficients of each construct were acceptable. In conclusion, the study obtained a fruitful questionnaire for unboxing the primary English language teacher’s TPACK profile.